Loss in forest resource values due to agricultural land conversion in Brazil - Ronaldo Serôa da Motta; Peter Herman May (Institute for Applied Economic Research (ipea), 2015)
This study presents a preliminary estimate of user costs of forestland conversion for agricultural purposes for the period 1970-80 in Brazil. In this initial version, only loss in potential sustainable wood output is considered. However, the analytical framework adopted here can be extended to incorporate other on-site forest products (rubber, nuts, etc.) and important off-site benefits such as biodiversity.
Keywords: 330